Gender-related gene expression in response to dietary fatty acids and predisposition to atherosclerosis and cardiovascular disease. (December 2011) - Rodriguez-Leyva, Delfin; Malik, Amrit; Tappia, Paramjit S
There is now overwhelming evidence that nutritional genomics has the potential to change dietary guidelines and personal dietary recommendations. While the field of nutrigenomics determines the impact of nutrients on the genome, proteome and metabolome, nutrigenetics, involves understanding the role of genetic variation in the interaction between diet and disease. It is evident that nutrigenetics has the potential to provide the basis for personalized dietary recommendations based on the individual''s genetic makeup. Although men and women share in common most of their genetic information, significant differences in susceptibilities to complex diseases such as atherosclerosis and cardiovascular disease exist. Accordingly, this review discusses the modulation of gene expression by dietary fatty acids in a gender-specific manner, which may open new approaches in dietary intervention of atherosclerosis and cardiovascular disease that are linked to sex.